2021
DOI: 10.3390/ph14050392
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Resistance Development in E. coli against TCAT, a Trimethoprim-Based Photoswitchable Antibiotic

Abstract: During the last decades, a continuous rise of multi-drug resistant pathogens has threatened antibiotic efficacy. To tackle this key challenge, novel antimicrobial therapies are needed with increased specificity for the site of infection. Photopharmacology could enable such specificity by allowing for the control of antibiotic activity with light, as exemplified by trans/cis-tetra-ortho-chloroazobenzene-trimethoprim (TCAT) conjugates. Resistance development against the on (irradiated, TCATa) and off (thermally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“… 41 Furthermore, they indicate that the observed differences in antibacterial activities might arise from other coexisting mechanisms (e.g., different accumulation in bacteria), as recently suggested by our follow-up study of resistance development against the best candidate. 42 Furthermore, a cheminformatics analysis of key physicochemical parameters revealed that these TMP derivatives have molecular weights and calculated log P s outside of the drug-like ranges ( SI , Section S5.3). Overall, despite being responsive to visible light, these previously designed compounds still offer major room for improvement and are an attractive starting point for structure-based design in photopharmacology.…”
Section: Resultsmentioning
confidence: 99%
“… 41 Furthermore, they indicate that the observed differences in antibacterial activities might arise from other coexisting mechanisms (e.g., different accumulation in bacteria), as recently suggested by our follow-up study of resistance development against the best candidate. 42 Furthermore, a cheminformatics analysis of key physicochemical parameters revealed that these TMP derivatives have molecular weights and calculated log P s outside of the drug-like ranges ( SI , Section S5.3). Overall, despite being responsive to visible light, these previously designed compounds still offer major room for improvement and are an attractive starting point for structure-based design in photopharmacology.…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, the same group studied the mechanism of resistance development in E. coli against the photoswitchable DHFR inhibitor 39. [44] While in vitro studies showed that 39 exhibits DHFR inhibitory activity analogous to that of the parent compound, transcriptome analysis indicated that the acquired resistance for the photochromic and classical DHFR inhibitors occurred via different mechanisms. In a follow-up study, Kobauri et al [43b] reported the IC 50 values for the photoswitchable DHFR inhibitors 37-39 (Figure 8).…”
Section: Light-responsive Dihydrofolate Reductase (Dhfr) Inhibitorsmentioning
confidence: 99%
“…An 8‐fold difference in antibacterial activity was observed against E. coli , in which MIC 50 values of >80 μM and 10 μM were obtained for 39‐ E and the photo‐enriched 39‐ Z form, respectively. In 2021, the same group studied the mechanism of resistance development in E. coli against the photoswitchable DHFR inhibitor 39 [44] . While in vitro studies showed that 39 exhibits DHFR inhibitory activity analogous to that of the parent compound, transcriptome analysis indicated that the acquired resistance for the photochromic and classical DHFR inhibitors occurred via different mechanisms.…”
Section: Light‐responsive Dihydrofolate Reductase (Dhfr) Inhibitorsmentioning
confidence: 99%
“…This resistance mechanism is used by bacteria resistant to trimethoprim and sulfonamides. The mechanism is based on a decrease in bacterial sensitivity and a decrease in the affinity of the enzymes dihydropteroate synthetase and dihydropteroate reductase (Lauxen et al 2021). Alteration of cell membrane permeability is a bacterial mechanism of resistance, which often occurs in gram-negative bacteria to certain water-soluble AB.…”
Section: Problems Of Antibiotic Resistance Of Bacteriamentioning
confidence: 99%